Sociological Analysis Of Islamic Law On Waqf Practices In Kyai Family In Bangkalan District - Taufiq Azizul Akbar; Muttaqin Choiri (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2021)
In this study, the researcher analyzed sociologically Islamic law regarding waqf practices that occurred in the kyai's family in Bangkalan. Waqf in the Kyai's family, namely waqf that occurs in one family or the nazhir is the same person as the wakif or from the same family as the wakif. Therefore, it is necessary to study the topic of how the practice of waqf in the Kyai's family in Bangkalan Regency, the majority of which have family waqf practices, including those from the Kyai's family. This study uses a qualitative approach, while data collection uses interviews and observations as well as documentation studies. And from this study it can be concluded that waqf in the Kyai's family, the practice of waqf in the Kyai's family in Bangkalan Regency is indeed like a tradition or culture that cannot be separated. This is due to the existence of patterns of behavior (law) of citizens, laws and behavior patterns as creations and manifestations of social groups, and the reciprocal relationship between changes in law and social and cultural changes. . In addition, the influence of Islamic law on society and changes in society and also the influence of change and development of society on Islamic legal thought which has been mentioned in the sociological thought of Islamic law.